Literary Translation as a Polemic Manifestation of Program Mindsets of Silver Age Trends (translations by V. Bryusov and N. Gumilyov) - A. A. Ustinovskaya (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The question of literary translation of poems that are important in the context of developing a new artistic strategy by the leaders of the poetic movements of the Silver Age is considered. The relevance of the study is due to the fact that the multicultural and multilingual dialogue of translators is analyzed both with the texts of the original and with each other. The results of a comparative analysis of poems by Paul Verlaine “Art Poétique” in the translation of Valery Bryusov and Teofil Gautier “L’Art” in the translation of Nikolai Gumilyov are presented. The author notes that Bryusov saw ideas that resonate with his idea of symbolism as a stylistic phenomenon in Verlaine’s work. Particular attention is paid to the fact that Verlaine is polemicizing with the previous tradition - the poetry of the Parnassians, whose principles were embodied in the work of Gautier. The question is raised that Nikolai Gumilev, translating Gautier, engaged in implicit controversy with both Bryusov and Verlaine. The author dwells on the fact that the background of this polemic is the justification of the “neoparnassian” and “neoclassical” foundations in the style and poetics of acmeism. It is proved that the purpose of this polemic is the manifestation of the program mindsets of symbolism (in Bruce's version) and acmeism (in Gumilev version) based on the authority of Verlaine and Gautier.